The STEM-based project-based learning impact on students' critical thinking skills - Novitasari, Aulia; Isnaini, Ludia Anggun; Supriyadi, Supriyadi (Univeritas Papua, 2024)
Education in the current era must be able to adapt to the development of society and technology. One important aspect that needs to be developed is students' critical thinking skills. However, this ability is often not well trained, as seen from the results of pre-research on students at MAN 1 Tanggamus which showed a low category. The study aims to test the effect of the STEM-based Project-Based Learning (PjBL) learning model on improving students' critical thinking skills. This study used a quasi-experimental pretest-posttest control group type. The study population included all students of class X MIA at MAN 1 Tanggamus, consisting of three classes. The sample was taken using the cluster random sampling method, where X MIA 2 was the experimental class and X MIA 1 was the control. Data were collected through interviews, documentation, and essay tests consisting of 15 questions. Data were calculated using the independent sample t-test. The research findings showed sig. = 0.00, which indicates that the STEM-based PjBL model has an impact on improving students' critical thinking skills.